The Ability of Aphis craccivora, A. gossypii and A. citricola to Transmit Single and Mixed Viruses to Cowpeas - Roberts, J.M.; Thottappilly, G.; Hodgson, C.J. (1993)
The ability of populations of adult apterous Aphis craccivora. A, gossypii and A, citricola to transmit the cowpea aphid-borne virus (CAMV) and cucumber mosaic virus (CMV) to cowpea was investigated. CMV was more readily transmitted than CAMV by all three aphid species, but was most readily transmitted hy A. craccivora andyl. citricola, with transmissions ranging from 64—71 %. With CAMV, the infection level with A. gossypii was higher than with A. craccivora and both were more efficient than A. citricola, although the differences were not significant. With mixed infections of CAMV and CMV, there was a higher level of CAMV transmission using yl. craccivora from sequential feeding when CMV-infected plants were fed on first followed by CAMV-infected plants, suggesting that cowpea plants were more prone to infection by CAMV when already infected by CMV.